FAKTOR-FAKTOR YANG MEMPENGARUHI KREATIVITAS KARYAWAN FRONTLINE - Nurofi, Achmad (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2014)
Given that importance of the frontline employees, and thus are in a privileged position to collect market information, as well as help their employer to develop better solutions to customer problems, it is important to understand the determinants of their creativity.            This research uses convinience sampling method. Respondent from this research are 109 persons, which are the frontliner of tour & travel in Semarang City. Data analyze tools which used in this research is Structural Equation Modeling (SEM) under AMOS 21 program.            Result from data analyzes shows that the model and the result from research can be accepted. And this result proves that influence of learning orientation, and creativity is positive and significant. Goal orientation influences positive and significant to creativity. And crativity influences positive and significant to performance.